Dynamical Coupling of Energetic Electrons and Upper‐Hybrid Thermal Fluctuations in the Earth's Radiation Belt. Issue 3 (18th March 2020) - Yoon, Peter H.; Hwang, Junga
Abstract: The inner magnetosphere including the radiation belt environment is replete with quasi‐electrostatic fluctuations with peak frequency in the upper‐hybrid frequency range. Some examples are demonstrated with the Van Allen Probe spacecraft data. These features have recently been explained in the framework of spontaneously emitted thermal noise theory. Such an environment is also characterized by quasi‐isotropic population of energized electrons, which naturally leads one to ask whether these electrons and the upper‐hybrid fluctuations influence each other. The present paper explores the potential causal relationship between the two features via kinetic theory. It is shown that indeed, isotropic energetic electrons and upper‐hybrid frequency thermal fluctuations can be dynamically coupled and that they could coexist in a quasi‐steady state manner. Key Points: Quiet time radiation belt is replete with thermal fluctuations in the upper‐hybrid frequency range It is also characterized by quasi‐isotropic energetic electron phase space distributions The present paper shows that thermal fluctuations and energetic electrons form dynamically coupled steady‐state solutions